2018
DOI: 10.1016/j.redox.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Cx26 partial loss causes accelerated presbycusis by redox imbalance and dysregulation of Nfr2 pathway

Abstract: Mutations in GJB2, the gene that encodes connexin 26 (Cx26), are the most common cause of sensorineural hearing impairment. The truncating variant 35delG, which determines a complete loss of Cx26 protein function, is the prevalent GJB2 mutation in several populations. Here, we generated and analyzed Gjb2+/− mice as a model of heterozygous human carriers of 35delG. Compared to control mice, auditory brainstem responses (ABRs) and distortion product otoacoustic emissions (DPOAEs) worsened over time more rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 103 publications
1
64
0
Order By: Relevance
“…The major results indicated that polyphenols administrated in conjunction with cisplatin can exert both anti-oxidant and pro-oxidant effects; however, the polyphenolic compounds show different mechanisms of action depending on cell context and dosage. In fact, cisplatin in the cochlea causes an excessive ROS production resulting in redox imbalance and cell death similarly to what occurs in noise-induced hearing loss and presbycusis 21,[34][35][36][37] . Here, we demonstrated that the increase of Nrf-2 nuclear translocation and HO-1 fluorescence in hair cells and spiral ganglion neurons (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The major results indicated that polyphenols administrated in conjunction with cisplatin can exert both anti-oxidant and pro-oxidant effects; however, the polyphenolic compounds show different mechanisms of action depending on cell context and dosage. In fact, cisplatin in the cochlea causes an excessive ROS production resulting in redox imbalance and cell death similarly to what occurs in noise-induced hearing loss and presbycusis 21,[34][35][36][37] . Here, we demonstrated that the increase of Nrf-2 nuclear translocation and HO-1 fluorescence in hair cells and spiral ganglion neurons (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This stands out a key open question for cochlear physiopathology, as connexin expression and spontaneous Ca 2+ signaling in the GER are essential for normal development of the sensory epithelium, hair cell functional maturation, hearing acquisition, [20][21][22][23] redox homeostasis and age-related hearing loss. 24 We are confident that the technological advances presented here have the potential to shed light on this as well as a plethora of other unrelated open issues that concern the role of paracrine signaling in physiology and pathology 93 and cannot be addressed with standard methods.…”
Section: Discussionmentioning
confidence: 92%
“…The null Cx26 can induce apoptosis and oxidative damage in the cochlear duct, reduce the release of glutathione from connexin hemichannels, and decrease nutrient delivery to the sensory epithelium via cochlear gap junctions, thereby leading to HL. Cx26-deficient mouse models showed congenital HL and cochlear developmental disorders [ 53 55 ]. GJB2 -related HL is usually binaural [ 42 , 56 ], as in all 244 patients in this study.…”
Section: Discussionmentioning
confidence: 99%